An attempt to eliminate the alienation of labor: interpretation of Marx's view of labor in the socialist countries’ legal practice - Linglan Xia; Maoyue Zhang (Trans/Form/Ação)
Karl Marx's critique of labor alienation remains a central theme in discussions on the exploitation of workers in capitalist societies. This study examines how socialist states — the Soviet Union, China and Cuba — attempted to institutionalize Marxist labor theory into their legal frameworks, focusing on collective ownership, the abolition of private property and labor relations. By employing a hermeneutic comparative analysis, this paper explores the contradictions between Marxist ideals and their practical application in socialist legal systems, particularly how bureaucratic structures and political interference shaped labor policies. While Marx's theory provides a theoretical foundation for eliminating alienation through collective ownership, this study highlights how real-world challenges hindered the creation of a fully anti-alienating legal order. Furthermore, the paper extends the discussion to modern labor concerns, including the gig economy, automation and neoliberal labor policies, demonstrating how Marxist critiques of labor remain relevant in contemporary legal scholarship. The findings suggest that legal structures, inspired by Marxist thought, often failed to fully empower workers, raising questions about the viability of anti-alienation policies in socialist labor systems.